Itinerary for Dr. Robert Hillestad visit - Unidentified author (Colorado State University. Libraries, 2003)
Itinerary for Betts' visiting scholar, Dr. Robert Hillestad, Ph.D. Includes typed and handwritten notes and schedule.
Keywords: Fashion -- History; Fashion -- Exhibitions